A Compact Bandpass Filter Using A T-Shaped Loaded Open-ended Stub Resonator - Ali Nyangwarimam Obadiah; Mohamad Rijal Hamid; Mohamad Kamal Abd Rahim; Noor Asniza Murad (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper proposes a compact bandpass filter using a loaded open-ended T-shaped stub. The open-ended T-shaped stub is loaded with vertical resonators placed across. The key advantage of using vertical resonators in the design is the simplicity and low insertion loss it provides. The structure used is an open-ended stub attached on one end to the transmission line (λ/2) to form a T-shaped resonator (λ/4) having vertical resonators placed across. The vertical resonator position alters the position at which the transmission zero occurs. A pair of the T-shaped resonator is placed on parallel sides of the feed line. The proposed filter is designed with the aid of Computer Simulation Technology Microwave Studio Software. The proposed concept is verified by designing filters with four different vertical resonator positions. The filter possesses a good rejection and low insertion loss of < 2dB with Chebyshev response. This filter is suited for modern-day communication applications since it shows good rejection of out of band signals.